2016
DOI: 10.1118/1.4949002
|View full text |Cite
|
Sign up to set email alerts
|

A clinically observed discrepancy between image‐based and log‐based MLC positions

Abstract: It has been clinically observed that log-file derived leaf positions can differ from their actual position by >1 mm, and therefore cannot be considered to be the actual leaf positions. This cautions the use of log-based methods for MLC or patient quality assurance without independent confirmation of log integrity. Frequent verification of MLC positions through independent means is a necessary precondition to trust log-file records. Intratreatment EPID imaging provides a method to capture departures from MLC pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 10 publications
5
69
0
Order By: Relevance
“…Initially, we started our investigations using the extended logging information of the linac for synchronization of the sub‐arcs, as described by Mans et al However, mainly due to the logging frequency and the lag of the system, synchronization based on this information resulted in less accurate results for sub‐arc dose delivery QA (data not presented). Similar problems with the accuracy of logging information have also been reported for Varian linacs . After applying our synchronization, we observed that the gantry angles were generally within 2° agreement with the ones recorded in the log files.…”
Section: Discussionsupporting
confidence: 81%
“…Initially, we started our investigations using the extended logging information of the linac for synchronization of the sub‐arcs, as described by Mans et al However, mainly due to the logging frequency and the lag of the system, synchronization based on this information resulted in less accurate results for sub‐arc dose delivery QA (data not presented). Similar problems with the accuracy of logging information have also been reported for Varian linacs . After applying our synchronization, we observed that the gantry angles were generally within 2° agreement with the ones recorded in the log files.…”
Section: Discussionsupporting
confidence: 81%
“…This study used the absolute difference between positions (c) and (d) for MLC performance quantitation. However, Neal et al 12 reported observed discrepancies between positions (b) and (d). We have not observed such discrepancies and cannot comment on this issue.…”
Section: Introductionmentioning
confidence: 97%
“…However, the EPID resolution of the Vero4DRT was 0.18 mm/pixel at the isocenter plane and this gave sufficient sensitivity to detect positional errors with submillimeter sizes. Furthermore, several researchers reported that Varian Dynalog files were not sufficient to detect MLC leaf position errors 17, 35. Zwan et al.…”
Section: Discussionmentioning
confidence: 99%